Protocolo para pruebas de seguridad eléctrica en equipos electro médicos: caso de estudio (2020)
In Colombia, the National Program of Technosurveillance, belonging to INVIMA, is the set of activities that allows the identification, evaluation, management and dissemination of information on incidents and adverse events due to the use of medical devices. However, with regard to the electrical safety of these devices, ICONTEC, according to Decree 2269 of 1993, adopted as a Colombian technical standard, what was proposed by the International Electrotechnical Commission (NTC/IEC 60601-1) to ensure the proper functioning of electromedical equipment. In this internship work, we intend to develop, with the company grandtek S.A.S, the study of the standard and create a verification and evaluation protocol, to guarantee the electrical safety tests of electromedical equipment. And thus be able to provide this service, to perform and certify the electrical safety tests on electromedical equipment that is part of a preventive maintenance program required by Decree 4725. The protocol is carried out in a series of stages and guidelines based on the standard. It is executed with Microsoft Excel formats. The tests are carried out at the San José Hospital, where the acquisition, processing and interpretation of the measurements of the tests performed is done, guaranteeing the correct functioning of a ventilator, defibrillator, sign monitor, electric bed and an electrocardiograph. With the development of the protocol it is expected to contribute to the reduction of electrical accidents and the strengthening of the management of the safety performance of the use of electromedical equipment.